2013
DOI: 10.1038/nature11868
|View full text |Cite
|
Sign up to set email alerts
|

Sodium chloride drives autoimmune disease by the induction of pathogenic TH17 cells

Abstract: There has been a marked increase in the incidence of autoimmune diseases in the last half-century. While the underlying genetic basis of this class of diseases has recently been elucidated implicating predominantly immune response genes1, changes in environmental factors must ultimately be driving this increase. The newly identified population of interleukin (IL)-17 producing CD4+ helper T cells (Th17 cells) plays a pivotal role in autoimmune diseases2. Pathogenic IL-23 dependent Th17 cells have been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

55
1,183
15
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,207 publications
(1,312 citation statements)
references
References 37 publications
55
1,183
15
14
Order By: Relevance
“…In agreement with these findings, T H 17 cells generated under salt‐enriched conditions show a highly pathogenic phenotype in vitro 74, 75. This increase in T H 17 responses under high salt conditions was shown to be mediated by p38 mitogen‐activated protein kinase (MAPK), nuclear factor of activated T cells (NFAT5), and serum glucocorticoid kinase‐1 (SGK1) 74, 75. Consistently, a T cell–specific knockout of Sgk1 in mice ameliorated EAE disease severity that was seen on a high salt diet 75.…”
Section: Salt and Mssupporting
confidence: 83%
See 3 more Smart Citations
“…In agreement with these findings, T H 17 cells generated under salt‐enriched conditions show a highly pathogenic phenotype in vitro 74, 75. This increase in T H 17 responses under high salt conditions was shown to be mediated by p38 mitogen‐activated protein kinase (MAPK), nuclear factor of activated T cells (NFAT5), and serum glucocorticoid kinase‐1 (SGK1) 74, 75. Consistently, a T cell–specific knockout of Sgk1 in mice ameliorated EAE disease severity that was seen on a high salt diet 75.…”
Section: Salt and Mssupporting
confidence: 83%
“…A possible explanation of these divergent results is the different treatments and baseline characteristics of the MS patients included in the studies, as well as the divergent approaches to assess sodium intake in these retrospective analyses. Several studies have shown that high sodium diets could exacerbate EAE 74, 75, 77, 79. When analyzing CD4 + T cells, this effect was accompanied by increased numbers of T H 17 cells and a higher infiltration of T H 17 cells into the CNS 74, 75.…”
Section: Salt and Msmentioning
confidence: 98%
See 2 more Smart Citations
“…48 A diet rich in salt is implicated as a possible cause of increased inflammation and the autoimmune response. 49 This may be partially due to the induction of pathogenic TH17 cells. 50 IL-17-producing CD4 (+) helper T cells are a newly described sub-population of T cells, and these cells have a pivotal role in autoimmune diseases.…”
Section: Adaptive Immune System In the Pathogenesis Of Hypertensionmentioning
confidence: 99%